VIRTUAL SCIENTIFIC WRITING ASSISTANCE FOR TEACHERS AS IMPLEMENTATION OF SUSTAINABLE PROFESSIONAL DEVELOPMENT - Melati, Inaya Sari; Harnanik, Harnanik (Universitas Negeri Semarang, 2020)
Salah satu permasalahan utama bagi guru di Indonesia adalah rendahnya kuantitas dan kualitas karya ilmiah yang dibuat oleh guru. Padahal ditinjau dari sisi administrasi, menulis karya ilmiah merupakan salah satu syarat utama bagi guru untuk kenaikan golongan kepangkatan guru sebagai bentuk pengembangan keprofesian berkelanjutan. Oleh karena itu, diperlukan pendampingan bagi guru dalam menulis karya ilmiah. Kegiatan pendampingan ini dilakukan secara virtual, sesuai dengan anjuran pemerintah untuk melakukan social distancing selama masa pandemi. Peserta pendampingan terdiri dari 214 guru dari berbagai jenjang pendidikan yang tersebar dari berbagai daerah di Indonesia. Metode pelaksanaan kegiatan pengabdian ini meliputi: (1) penyampaian materi mengenai Karya Tulis Ilmiah (KTI); (2) pemberian pemahaman mengenai pentingnya menulis karya ilmiah bagi guru dan tenaga pendidik; (3) sesi diskusi dan tanya jawab dengan memberikan kesempatan bagi guru dan tenaga pendidik terkait penulisan karya ilmiah; (4) memberikan gambaran dan simulasi tentang penulisan karya ilmiah; (5) evaluasi hasil dari kegiatan yang telah dilakukan. Tanggapan peserta dalam kegiatan ini sangat antusias, sehingga direncanakan kegiatan lanjutan berupa bimbingan teknis penulisan KTI secara lebih intensif. One of the main problems for teachers in Indonesia is the low quantity and quality of scientific work made by teachers. Whereas in terms of administration, writing scientific work is one of the main requirements for teachers to increase the rank of teachers as a form of sustainable professional development. Therefore, assistance is needed for teachers in writing scientific work. This mentoring activity is carried out virtually, in accordance with the government's recommendation to conduct social distancing during the pandemic. The mentoring participants consisted of 214 teachers from various levels of education spread from various regions in Indonesia. Methods of implementation of this devotional activities include: (1) the delivery of material on Scientific Papers (KTI); (2) providing an understanding of the importance of writing scientific work for teachers and educators; (3) discussion and question and answer sessions by providing opportunities for teachers and educators related to the writing of scientific works; (4) provide an overview and simulation of the writing of scientific works; (5) evaluation of the results of the activities that have been carried out. The response of participants in this activity was very enthusiastic, so that the planned follow-up activities in the form of technical guidance on writing KTI more intensively.